Cell lineage tracing and functional assessment of supraspinatus tendon healing in an acute repair murine model. Issue 8 (15th June 2020) - Moser, Helen L.; Abraham, Adam C.; Howell, Kristen; Laudier, Damien; Zumstein, Matthias A.; Galatz, Leesa M.; Huang, Alice H.
Abstract: Rotator cuff supraspinatus tendon injuries are common with high rates of anatomic failure after surgical repair. The purpose of the study was to define clinically relevant features of a mouse model of supraspinatus tendon injury to determine painful, functional, and structural outcomes; we further investigated two cell populations mediating healing using genetic lineage tracing after full detachment and repair of the supraspinatus tendon in mice. The pain was assessed using the mouse grimace scale and function by gait analysis and tensile testing. Histological and microCT analyses were used to determine enthesis/tendon and bone structure, respectively. Lineage tracing was carried out using inducible Cre lines for ScxCreERT2 (tendon cells) and αSMACreERT2 (myofibroblasts and mesenchymal progenitors). Mice only expressed pain transiently after surgery despite long‐term impairment of functional and structural properties. Gait, tensile mechanical properties, and bone properties were significantly reduced after injury and repair. Lineage tracing showed relatively few Scx lin tendon cells while αSMA lin cells contributed strongly to scar formation. Despite surgical reattachment of healthy tendon, lineage tracing revealed poor preservation of supraspinatus tendon after acute injury and loss of tendon structure, suggesting that tendon degeneration is also a key impediment of successful rotator cuff repair. Scar formation after surgery is mediated largely by αSMA lin cells and results in permanently reduced functional and structural properties.